First Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 22-27,1987. Day 3. Plenary session. Tape 1 of 3. - Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology, 1987)
Dr. House states that the aim is to provide a constructive critique of education and to point to some directions where the education system should be heading. He gives some background about the general vision of the future as envisioned in the report and Wayne Humphries addresses in more specific detail what the role of education should be. Opening credit says Royal Commission on Education & Youth; Dr. G.L. Parsons introduces the speakers.